Large wood clogging during floods in a gravel‐bed river: the Długopole bridge in the Czarny Dunajec River, Poland. Issue 3 (13th January 2017) - Ruiz‐Villanueva, Virginia; Wyżga, Bartłomiej; Mikuś, Paweł; Hajdukiewicz, Maciej; Stoffel, Markus
Abstract: During floods, large quantities of wood can be mobilized and transported downstream. At critical sections, such as bridges, the transported wood might be entrapped and a quick succession of backwater effects can occur as a result of the reduction of the cross‐sectional area. The aim of this work is to explore large wood‐related hazards during floods in the gravel‐bed river Czarny Dunajec (Polish Carpathians), where the river flows through the village of Długopole. This work is based on the numerical modelling of large wood transport together with flow dynamics in which inlet and boundary conditions were designed based on field observations. The exploratory approach developed in this study uses multiple scenarios (193) to analyse the factors controlling bridge clogging: wood size, wood supply, flow conditions, morphology and obstacles in the riverbed. Results highlighted the strong control of log length (stronger than that of log diameter) on potential blockage probability; however, according to our results the main factor controlling bridge clogging was the flood discharge. River morphology and wood supply play an important role as well. The river morphology may reduce bridge blockage, as it influences flow velocity and depth, and creates natural retention zones for wood. In addition, the impacts of bridge blockage were analysed in terms of afflux depth and length, and flooded area. Results showed that bridge blockage may result in a significant increase in water depth (up to 0.7 m) and flooded area (up to 33% more), therefore increasing flood risk in the village. Copyright © 2016 John Wiley & Sons, Ltd.